TiO2 bunchy hierarchical structure with effective enhancement in sodium storage behaviors. Issue 4 (27th February 2022) - Liu, Shen; Niu, Kai; Chen, Shuailin; Sun, Xin; Liu, Lehao; Jiang, Bing; Chu, Lihua; Lv, Xiaojun; Li, Meicheng
Abstract: Bronze phase TiO2 [TiO2 (B)] has great research potential for sodium storage since it has a higher theoretical capacity and ion mobility compared with other phases of TiO2 . In this case, preparing porous TiO2 (B) nanosheets, which can provide abundant sodium insertion channels, is the most effective way to improve transport kinetics. Here, we use the strong one‐dimensional TiO2 nanowires as the matrix for stringing these nanosheets together through a simple solvothermal method to build a bunchy hierarchical structure [TiO2 (B)‐BH], which has fast pseudocapacitance behavior, high structural stability, and effective ion/electron transport. With the superiorities of this structure design, TiO2 (B)‐BH has a higher capacity (131 vs. 70 mAh g −1 [TiO2 ‐NWs] at 0.5 C). And it is worth mentioning that the reversible capacity of up to 500 cycles can still be maintained at 85 mAh g −1 at a high rate of 10 C. Meanwhile, we also further analyzed the sodium storage mechanism through the ex‐situ X‐ray powder diffraction test, which proved the high structural stability of TiO2 (B)‐BH in the process of sodiumization/de‐sodiumization. This strategy of uniformly integrating nanosheets into a matrix can also be extended to preparing electrode material structures of other energy devices. Abstract : TiO2 bunchy hierarchical structure has fast pseudocapacitance behavior, effective ion/electron transfer pathway, and high structural stability, resulting in a good electrochemical performance for sodium batteries. This orderly integration strategy of nanosheets can be extended to the structure construction of electrode materials for other energy devices.